Prefrontal cortex glutamatergic adaptations in a mouse model of alcohol use disorder - Mahum T. Siddiqi; Dhruba Podder; Amanda R. Pahng; Alexandria C. Athanason; Tali Nadav; Chelsea Cates-Gatto; Max Kreifeldt; Candice Contet; Amanda J. Roberts; Scott Edwards; Marisa Roberto; Florence P. Varodayan (Addiction Neuroscience, 2023)
Alcohol use disorder (AUD) produces cognitive deficits, indicating a shift in prefrontal cortex (PFC) function. PFC glutamate neurotransmission is mostly mediated by α-amino-3‑hydroxy-5-methyl-4-isoxazolepropionic acid-type ionotropic receptors (AMPARs); however preclinical studies have mostly focused on other receptor subtypes. Here we examined the impact of early withdrawal from chronic ethanol on AMPAR function in the mouse medial PFC (mPFC). Dependent male C57BL/6J mice were generated using the chronic intermittent ethanol vapor-two bottle choice (CIE-2BC) paradigm. Non-dependent mice had access to water and ethanol bottles but did not receive ethanol vapor. Naïve mice had no ethanol exposure. We used patch-clamp electrophysiology to measure glutamate neurotransmission in layer 2/3 prelimbic mPFC pyramidal neurons. Since AMPAR function can be impacted by subunit composition or plasticity-related proteins, we probed their mPFC expression levels. Dependent mice had higher spontaneous excitatory postsynaptic current (sEPSC) amplitude and kinetics compared to the Naïve/Non-dependent mice. These effects were seen during intoxication and after 3–8 days withdrawal, and were action potential-independent, suggesting direct enhancement of AMPAR function. Surprisingly, 3 days withdrawal decreased expression of genes encoding AMPAR subunits (Gria1/2) and synaptic plasticity proteins (Dlg4 and Grip1) in Dependent mice. Further analysis within the Dependent group revealed a negative correlation between Gria1 mRNA levels and ethanol intake. Collectively, these data establish a role for mPFC AMPAR adaptations in the glutamatergic dysfunction associated with ethanol dependence. Future studies on the underlying AMPAR plasticity mechanisms that promote alcohol reinforcement, seeking, drinking and relapse behavior may help identify new targets for AUD treatment.